PENGARUH STRUKTUR, BIAYA OPERASIONAL DAN PERENCANAAN PAJAK TERHADAP PAJAK PENGHASILAN BADAN TERUTANG - Apipih Apipih; Endah Finatariani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of capital structure, operational costs and tax planning on corporate income tax payable partially and simultaneously in property and real estate companies listed on the BEI in 2018-2022. This research is quantitative research. In this study, the sample was taken using a purposive sampling technique based on predetermined criteria so that 11 companies were obtained. The data analysis method was carried out using panel data regression analysis with the help of Eviews version 12. The results of the study showed a partial hypothesis calculation that capital structure did not have a significant effect on corporate income tax payable with a significant level of 0.4240 > 0.05. Operational costs have a significant effect on corporate income tax payable with a significant level of 0.0036 < 0.05. Tax planning does not have a significant effect on corporate income tax payable with a significant level of 0.0782 < 0.05. The results of simultaneous testing or the F test show that capital structure, operational costs, tax planning together influence the corporate income tax payable with an F-count of 3.802099 with a probability of 0.015510 < 0.05.